Tatuagem : história e contemporaneidade - Lima, Rodrigo Muniz de Souza (2020)
We can agree that three of the major characteristics found out on all big cities across the globe are: the growing freedom and mobility, the easiness to communicate and the unstoppable technology updates, each day that goes by people are less scared of expressing themselves and sharing information. Those are some of the factors that gradually helped making practices like tattooing so popular in the XXI century, transforming it into a vigorous business with huge market potential and it’s still growing further, providing lots of space for new tattooers and apprentices to show up and help supplying the demand for tattoos. Until the end of the 20th century it wasn’t as popular because tattooing was often seen as some underground scene, therefore the tattoo studios back then wouldn’t train a lot of apprentices nor draw themselves too much attention, there weren’t loads of clients like there’s today so the competition between studios could get messy. That scenario only starts to change into a burst growth around 2004 when the world has wide access to the internet and social media, tattoo reality shows are all around and tattoo artists begin to share their lifestyles and work with the society. At this same time a lot of people got interested by the art of tattoing, free tattoo tutorials started to show up on the internet, especially on Youtube, expensive tattoo courses also started to show up. It happened in such a way that it all contributed to some unique historical phenomenon where, for the first time, the situation looks like this: a lot of people (inside the urban context) want to be tattooed; a lot of artists and people without artistic background are becoming tattooers, they’re trying to learn it every way they can; and for reasons that will be enlightened along this research, nowadays it’s a lot easier to do both. Our goal here is to analyze the tattoo history in order to fully understand why it’s becoming something huge in the 21st century and how it’s affecting as well as how it’s being affected by the most recent changes, therefore we’ll discuss elements like: the historical origins of the mass growth experimented recently, it’s effects on contemporary tattooing and society, tattoo concepts, practical details, how people are learning to tattoo and what are the sources of information, as well how serious it’s being taken, and finally the tattoo professional license and regulation.